2021
DOI: 10.1103/physrevb.103.085107
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electronic inhomogeneity of superconducting Nb-doped Bi2Se3

Abstract: The crystal structure, electronic structure, and transport properties of crystals with the nominal composition Nb 0.25 Bi 2 Se 3 are investigated. X-ray diffraction reveals that the as-grown crystals display phase segregation and contain major contributions of BiSe and the superconducting misfit layer compound (BiSe) 1.1 NbSe 2 . The inhomogeneous character of the samples is also reflected in the electronic structure and transport properties of different single crystals. Angle-resolved photoemission spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 47 publications
3
6
0
Order By: Relevance
“…Rather, it is found to primarily be located in the misfit phase. Our findings are in good agreement with recent reports linking the origin of superconductivity to the presence of the misfit phase [30,31].…”
Section: Introductionsupporting
confidence: 93%
See 3 more Smart Citations
“…Rather, it is found to primarily be located in the misfit phase. Our findings are in good agreement with recent reports linking the origin of superconductivity to the presence of the misfit phase [30,31].…”
Section: Introductionsupporting
confidence: 93%
“…Despite the lack of clarity on the origin of the reduced amplitude of the EXAFS oscillations, the sum of the evidence suggests a strong tendency toward the formation of the misfit phase rather than incorporation of Nb dopants into the Bi 2 Se 3 host structure. In a recent study [30], we estimated that the total phase content across a crystal boule (from which S1 originates) fits approximately with the assumption that all or most of the Nb in the synthesis appear in the misfit phase. We also found that all superconducting samples contained this phase.…”
Section: Variablesmentioning
confidence: 91%
See 2 more Smart Citations
“…However, to which extent the observed two-fold symmetric superconductivity is originated from an intrinsic topological nature still re- * mingquan.he@cqu.edu.cn mains elusive. Other factors, such as built-in strain or distortion [17,18], structural inhomogeneity and impurity phases [19][20][21][22], inhomogeneously distributed superconducting regions [4,16,[23][24][25], cannot be completely ruled out at this stage. Exclusion of possible extrinsic origins is of great importance to clarify the putative topological nature of the nematic superconductivity found in doped Bi 2 Se 3 systems.…”
Section: Introductionmentioning
confidence: 99%